CULTURAL ALLUSIONS AND HUMOROUS EFFECTS OF OCCULT DEPICTIONS IN NIGHT FERRY - Aiqing Wang (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
??? Yehang Chuan ‘Night Ferry’ is an encyclopaedic masterpiece and the chef-d’oeuvre of ?? Zhang Dai (circa 1597-1689), an illustrious historian, poet, dramatist, essayist, aesthete, musician and gastronomist in late Ming and early Qing China. Night Ferry cumulates more than four thousand entries and encompasses a veritable cornucopia of topics in an elephantine range. In this research, I investigate Chapter Twenty ?? Fang Shu ‘Alchemy and Sorcery’ of Night Ferry, which comprises Section ?? Fu Zhou ‘Amulets and Incantations’ and Section ?? Fang Fa ‘Prescriptions and Practices’. Both sections abound with depictions pertaining to occult acts and paranormal forces, the vast majority of which embody cultural allusions concerning religion, divination and patriarchy. Furthermore, Chapter ‘Alchemy and Sorcery’ is featured by humorousness, though Night Ferry is not a dedicated jestbook. The humorous effect in Night Ferry is not attained via sarcasm or homo-/hetero-erotism, as manifested by derisive and prurient jokes compiled in a renowned pre-modern jestbook entitled ????Xiao Lin Guang Ji ‘A Collection of Classic Chinese Jokes’.